1977
DOI: 10.1002/1097-0142(197701)39:1<255::aid-cncr2820390139>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle tumors of the gastrointestinal tract and retroperitoneum.A pathologic analysis of 100 cases

Abstract: One hundred smooth muscle tumors arising in the gastrointestinal tract and retroperitoneum were reviewed in an attempt to define criteria for the diagnosis of leiomyosarcoma in these sites. On the basis of aggressive behavior, 56 of these neoplasms were diagnosed as leiomyosarcoma. Mitoses were found to be the most useful indicator of malignancy; all of the tumors with five or more mitoses/10 HPF behaved aggressively and smooth muscle tumors with this degree of mitotic activity should be diagnosed as leiomyosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
2
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(106 citation statements)
references
References 17 publications
3
99
2
2
Order By: Relevance
“…Similarly, Ranchod and Kempson observed that marked cytologic atypia was not a frequent finding in leiomyosarcomas but when present, was found only in malignant tumours and was associated with abundant mitoses. 13 Most leiomyomas in their study showed mild or no atypia, a feature shared by very low risk and low risk tumours in the present study. Also in the study by Evans both low and high grade leiomyosarcomas showed mostly moderate degree of nuclear atypia.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, Ranchod and Kempson observed that marked cytologic atypia was not a frequent finding in leiomyosarcomas but when present, was found only in malignant tumours and was associated with abundant mitoses. 13 Most leiomyomas in their study showed mild or no atypia, a feature shared by very low risk and low risk tumours in the present study. Also in the study by Evans both low and high grade leiomyosarcomas showed mostly moderate degree of nuclear atypia.…”
supporting
confidence: 53%
“…Most of the earlier studies have expressed MR/10HPFs as originally described by Ranchod and Kempson. 8 They advocated examination of 5 sets of 10 HPFs and the set with highest mitotic count was used as the final rate. This method allows for regional variation in MR that is typical of GIST.…”
Section: Discussionmentioning
confidence: 99%
“…GIST can occur along the gastrointestinal tract, most commonly in stomach (70%) (10,28,29) and small intestine (20%-25%) (10,28,31) . The clinical presentation depends on the site of the tumor and almost 20% of them may be asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 688 primary retroperitoneal tumors, 1% -2% were leiomyomas (6). Other studies have shown that most retroperitoneal smooth muscle tumors are malignant (7,8). A review of the literature from 1966 to 2008 confirmed that retroperitoneal myomas are extremely rare (9).…”
Section: Introductionmentioning
confidence: 95%